The challenges of urban planning in the tourist-historic city. A review of the book Barrera-Fernández, D. Attracting visitors to ancient neighbourhoods. Creation and management of the tourist-historic city of Plymouth, UK. Groningen: InPlanning, 2016. - Gastal, Susana de Araujo (El Periplo Sustentable; Núm. 38 (2020): Número Treinta y ocho, 2020)
Plymouth, UK, houses, for its strategic location, an important base of the British Navy. In recent times, the military presence in the city has been reduced, with impacts on the local economy. The book sign by Barrera-Fernández, Attracting visitors to ancient neighbourhoods - Creation and management of the tourist-historic city of Plymouth, UK analyses this scenario and the community solutions to the problem. It seems important to invest in regenerating port facilities, encouraging the installation in these spaces of leisure activities, shopping facilities and complementary products such as creative economy districts, and the celebration of big events.